Zur Rezeption von Paul Celans Werk in Manfred Winklers Lyrik - Rychlo, Petro Vasylʹovyč (Naharaim, 2025)
This article deals with one of the aspects of the lyrical work of the German-Hebrew poet Manfred Winkler from Bukovina - the poetic reception of Paul Celan’s work. Winkler’s long-standing preoccupation with lyrical texts and the human person of his great compatriot was expressed in the constant presence of Celanian poetic images, motifs, and forms in the appropriation of his poetic discoveries (coagulation principle, compressed pictorial structures, staccato rhythm, rich sound painting), and in the translation of Celan's groundbreaking poetry into Hebrew. All this takes place in the mode of allusions, reminiscences, quotations, and other intertextual forms, the adoption of the poem titles and individual lines of poetry as mottos for his texts, in numerous dedications of his poems to the older poet friend and master. It is no exaggeration to say that Celan was the paradigmatic poet for Winkler, who noticeably determined the direction of his poetic development.